Risk Factors and Clinical Manifestations of Juxtacortical Small Lesions: A Neuroimaging Study - Shan, Yilong; Tan, Sha; Wang, Yuge; Li, Kui; Zhang, Lei; Liao, Siyuan; Zhou, Li; Deng, Zhezhi; Hu, Xueqiang; Li, Haiyan; Men, Xuejiao; Zhang, Bingjun; et al. (Frontiers in Neurology, 2017)
Background and objective: White matter hyperintensities can be easily identified by brain imaging. Juxtacortical small lesions (JCSLs) are a special type of white matter lesion (WML), defined as no greater than 5 mm in diameter and adjacent to the cerebral cortex in location. We notice lately that JCSLs alone may be associated to various neurological symptoms. Here we design the present study to determine the risk factors for JCSLs and their clinical manifestations in patients in our neurology clinic. Methods: 206 participants suffered from neurological disorders and completed magnetic resonance imaging (MRI) examinations were divided into two groups: patients with JCSLs and patients without lesions on MRI. Meanwhile, 129 age- and sex-matchedhealthyvolunteers were also recruited. Laboratory examinations and the phenotypes and distributions of the symptoms of the three groups were compared. Results: The serum levels of apoB and HCYwere independently related to the appearance of JCSLs and HCY level was also associated with the number of JCSLs. Patients with JCSLs might presented with headache, insomnia, and/or anxiety/depression, which were related with the anatomical locations of the lesions. Conclusion: These data suggest that JCSLs are symptomatic and might result fromarteriole atherosclerosis, which should raise our attention.